Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538878
|View full text |Cite
|
Sign up to set email alerts
|

Peer instruction contributes to self-efficacy in CS1

Abstract: Recent work in computing suggests that Peer Instruction (PI) is a valuable interactive learning pedagogy: it lowers fail rates, increases retention, and is enjoyed by students and instructors alike. While these findings are promising, they are somewhat incidental if our goal is to understand whether PI is "better" than lecture in terms of student outcomes. Only one recent study in computing has made such a comparison, finding that PI students outperform traditionallytaught students on a CS0 final exam. That wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(38 citation statements)
references
References 31 publications
(26 reference statements)
0
35
1
Order By: Relevance
“…However, even in classes employing these instructional practices, there appears to be a vast divide among the students who succeed and those who fail. For example, researchers have shown independent of pedagogical style that students with prior experience in programming fare much better than those without prior experience [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, even in classes employing these instructional practices, there appears to be a vast divide among the students who succeed and those who fail. For example, researchers have shown independent of pedagogical style that students with prior experience in programming fare much better than those without prior experience [17].…”
Section: Introductionmentioning
confidence: 99%
“…N/A denotes data not available. CS, a number of studies have reported on the success of PI, including improved student satisfaction [5,8,10], student learning [7,15], final exam grades [11,13], failure rates [6], and retention of majors [9].…”
Section: Related Workmentioning
confidence: 99%
“…Students value PI [5,8,10] and learn more in PI classes compared to traditional lecture classes [11,13]. PI is also associated with low failure rates [6] and increased retention of majors [9].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research shows that students with no prior programming experience ("beginners") perform more poorly than students with experience [11,4]. In the inverted offering, students participated in supported classroom practise three times a week and prepared for these activities by watching videos.…”
Section: Beginnersmentioning
confidence: 99%